Efektivitas Azolla microphylla dalam Menurunkan COD, TSS dan BOD Air Lindi TPA - , Irhamni; Murtaja, Rian; Yahya, Husnawati; Erdiwansyah, Erdiwansyah (Jurnal Serambi Engineering, 2025)
Leachate is a liquid waste formed due to water seepage into waste piles containing high concentrations of organic and inorganic compounds that have the potential to pollute the environment. This study aims to evaluate the effectiveness of Azolla microphylla plants in reducing leachate pollutant parameters from the Blang Bintang TPA through the phytoremediation method. Variations of treatments include plant masses of 300 and 400 grams and residence times of 7 and 14 days. The parameters analyzed include Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and Biochemical Oxygen Demand (BOD). The results showed that the best treatment was obtained at a plant mass of 400 grams with a retention time of 14 days, with the effectiveness of reducing COD by 22.95% (from 758 mg/L to 584 mg/L), TSS by 60.80% (from 523 mg/L to 205 mg/L), and BOD by 22.40% (from 424 mg/L to 329 mg/L). Although it has not met the leachate quality standards based on Permen LHK No. 59 of 2016, the use of Azolla microphylla shows potential as an environmentally friendly phytoremediation agent. It can be further developed as part of a sustainable leachate treatment system.